Shank2 Regulates Renal Albumin Endocytosis. Issue 9 (2nd September 2015) - Dobrinskikh, Evgenia; Lewis, Linda; Doctor, R. Brian; Okamura, Kayo; Lee, Min Goo; Altmann, Christopher; Faubel, Sarah; Kopp, Jeffrey B.; Blaine, Judith
Abstract Albuminuria is a strong and independent predictor of kidney disease progression but the mechanisms of albumin handling by the kidney remain to be fully defined. Previous studies have shown that podocytes endocytose albumin. Here we demonstrate that Shank2, a large scaffolding protein originally identified at the neuronal postsynaptic density, is expressed in podocytes in vivo and in vitro and plays an important role in albumin endocytosis in podocytes. Knockdown of Shank2 in cultured human podocytes decreased albumin uptake, but the decrease was not statistically significant likely due to residual Shank2 still present in the knockdown podocytes. Complete knockout of Shank2 in podocytes significantly diminished albumin uptake in vitro. Shank2 knockout mice develop proteinuria by 8 weeks of age. To examine albumin handling in vivo in wild‐type and Shank2 knockout mice we used multiphoton intravital imaging. While FITC‐labeled albumin was rapidly seen in the renal tubules of wild‐type mice after injection, little albumin was seen in the tubules of Shank2 knockout mice indicating dysregulated renal albumin trafficking in the Shank2 knockouts. We have previously found that caveolin‐1 is required for albumin endocytosis in cultured podocytes. Shank2 knockout mice had significantly decreased expression and altered localization of caveolin‐1 in podocytes suggesting that disruption of albumin endocytosis in Shank2 knockouts is mediated via caveolin‐1. In summary, we have identified Shank2 as another component of the albumin endocytic pathway in podocytes.